Transcriptomic and proteomic analysis of Locusta migratoria eggs at different embryonic stages: Comparison for diapause and non-diapause regimes - Kun HAO; Jie WANG; Xiong-bing TU; Douglas W. Whitman; Ze-hua ZHANG (Journal of Integrative Agriculture, 2017)
Abstract: Temperate-zone insects typically survive winter by entering diapause. Although many aspects of insect diapause have been studied, the underlying molecular mechanism of insect diapause is not well understood. Here we report the results of the transcriptional and translational differences of migratory locust eggs at different embryonic states using diapause (low temperature) and non-diapause (high temperature) regimes. Compared with non-diapause eggs at 100 degree-days (N2) treatment, 29 671 transcripts and 296 proteins were differentially expressed at the diapause maintenance stage (D2). While compared with 150 degree-days (N3) treatment, 45 922 transcripts and 404 proteins were differentially expressed in the post-diapause stage (D3). Among them, 51 and 102 transcripts had concurrent transcription and translation profiles in D2 vs. N2 and D3 vs. N3 treatments, respectively. Analysis of Gene Ontology categorized these genes and proteins into three categories: biological processes, cellular components, and molecular functions. Biological pathway analysis indicated that three pathways: (1) insect hormone biosynthesis (KEGG: Map 00981), (2) the insulin signaling pathway (KEGG: Map 04910), and (3) the peroxisome proliferator-activated receptor (PPAR) signaling pathway (KEGG: Map 03320) play an important role in locust diapause regulation. Most of these transcripts and proteins were up-regulated in the diapause treatments, and were highly linked to juvenile hormone biosynthesis, insulin and PPAR signaling pathways, suggesting these three pathways may be involved in diapause and development regulation. This study demonstrates the applicability of high-throughput omics tools to identify biochemical pathways linked to diapause in locust egg development. In addition, it reveals that cellular metabolism in diapause eggs is more inactive than in non-diapause eggs, and most of the down-regulated enzymes and pathways are related to reduce energy loss.